Love at Web-Sight: The Adoption of Online Dating Website - Tsai, Chia-Shan (2014)
The Internet has revolutionised every aspect of our existence in ways which would have seemed impossible a few decades ago. One such revolution has come in the form of Internet dating, making romance attainable within just a few clicks. The service has seen a massive increase in popularity as recent generations increasingly rely upon the Internet for social interaction (IBIS World, 2014). As dating is one of the most intimate of human interactions, its digitalisation makes for an interesting research topic. The ultimate aim of this study is to analyse individual's intention towards adopting online dating. This paper will do this by examining the issue from the perspective of both the matching-making website and the potential adopter. The Diffusion of Innovation Theory will be used as a reference point in this study, allowing us to examine how various ideas may have influenced the intentions of Internet dating, ideas such as: Personal Innovativeness in the Domain of Information Technology (PIIT), relative advantage, compatibility and complexity. This study will also examine the potential role of PIIT as a moderator in this otherwise human-oriented phenomenon. The quantitative methodology used for this research was that of the web-based survey; this allowed for the collection of primary data which could then be analysed further. Such further analysis included descriptive analysis, analysis of variance (ANOVA), reliability analysis, validity analysis, Pearson correlation analysis and multiple regression analysis. The results of this study showed that the adoption intention of an individual was closely linked to a number of studied factors, including PIIT, relative advantage, compatibility and complexity. However, significant moderation was only found for PIIT on relative advantage and compatibility. Possible explanations for these results, as well as their managerial implications and suggestions, are provided.